Cosa Nostra and Camorra: illegal activities and organisational structures. Issue 1 (2nd January 2016) - Scaglione, Attilio
Abstract : This article intends to develop an introductory reflection concerning the most recent trends of two of the major Italian mafia organisations: the Sicilian Cosa Nostra and the Campanian Camorra. Following a comparative perspective, the analysis will focus the attention on changes that have occurred in recent years both at the level of illegal activities and at the level of organisational structures. After the bombs of the nineties, Cosa Nostra has moved towards a flexible and less centralised organisation, investing dirty money in the legal economic sector, to reduce its exposure to law enforcement investigations. At the same time, the Camorra clans have considerably widened their range of activity both at a local and international level.